End-Of-Life Decision Making A Novel Entrustable Professional Activity? - Mahmood, Maria (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2022)
Introduction: Making tough decisions about End-Of-Life situations and palliative care in acute surgical scenarios is a non-technical skill surgeons have to master over a number of years of experience. Data suggests that surgeons show a delayed referral to palliative care and admit to having a potentially curative approach. This skill has not been studied as an Entrustable Professional Activity and no attempts made at designing an assessment method. Our study aimed at creating and validating an assessment tool for EOL decision-making in surgery. Methods: Systematic reviews focused on surgical professionalism, clinical decision-making, and End-Of-Life care were conducted to lay the foundation for this project. Informed by the systematic reviews, a detailed reflective survey questionnaire including clinical vignettes based on frequently encountered scenarios in surgical practice was conducted for understanding the perceptions and practices of surgeons around EOL decision-making and palliative care. A clinical scenario was constructed and piloted among surgeons in a university teaching hospital for construct validity, scored by two independent examiners. Following the development of construct validity, this scenario was then conducted as part of the formal assessment in a high-stakes fellowship examination at a nodal point of transition to autonomous practice. Results: Systematic reviews highlighted the lack of data around non-technical elements including formative or summative assessment of EOL decision-making in surgical practice. Reflective survey questionnaire including the clinical vignettes highlighted; a rising level of comfort regarding EOL decision-making with the increasing number of years of experience, inadequate training opportunities, and statistically significant differences in perceptions and practices around EOL decision-making between senior and junior surgeons. The simulated assessment station piloted at a university teaching hospital achieved construct validity with consultants and registrars in their senior years of training scoring significantly higher than junior surgeons in their factors considered for EOL decision making (p=0.004). The same assessment tool when conducted in a high-stakes fellowship examination found that surgeons at the nodal point of transition to autonomous practice scored lower than senior consultants with years of practical experience in the field in aspects of EOL decision-making and communication regarding palliative decisions (p=0.02). Conclusion: With bespoke clinical scenarios orchestrated in a simulated environment, it is possible to assess clinical decision-making and analyse high-end decision-making at nodal points of transition to autonomous practice. Simulated assessment in a similar manner can be employed for formative and summative assessments of EOL decision-making.
APPROVED
Keywords: Palliative care; Surgery; Assessment; Entrustable Professional Activity; End-of-Life Decision Making